A Thanatopolitical Reading of Bandada de pájaros: segundo ensayo sobre la memoria by Jorgelina Cerritos - Leandro Hernández, Lucía (2021)
This article makes a reading of the dramaturgical work Bandada de pájaros: segundo ensayo sobre la memoria (2016) by Jorgelina Cerritos (San Salvador, 1974) from a thanatopolitical perspective. It inquires about the power exercised by the Salvadoran State in the life of the citizens, represented by characters who, deprived of their category of person, see all their rights interrupted. These subjects are members of a community who become a potential threat to be suppressed by the State. Furthermore, it analyzes the vulnerability of women to the heteropatriarchal warlike apparatus and the possibilities of theater as a space for the construction of a memory that restores the memory and identity of the thousands of disappeared during the Salvadoran civil war.